The Anthropocene (and) (in) the Humanities: Possibilities for Literary Studies - Savi, Melina Pereira (Revista Estudos Feministas, 2017)
This paper aims to briefly discuss the concept of the Anthropocene within the geological sciences, and to consider, more broadly, some of the theoretical unfolding of the term within the humanities. Towards its conclusion, the paper presents the demands the Anthropocene makes, as a geological Epoch (in which the human becomes a geophysical force, capable of changing the Earth’s biophysical systems), of literary studies as a possible field for theoretical articulations that may add to the debates on this historical moment in which climate change, forced dislocations, the mass extinction of several species, and other urgent matters come to the fore.